1993
DOI: 10.1165/ajrcmb/9.4.429
|View full text |Cite
|
Sign up to set email alerts
|

BQ123, an ETA Receptor Antagonist, Inhibits Endothelin-1-mediated Proliferation of Human Pulmonary Artery Smooth Muscle Cells

Abstract: Endothelin (ET-1) has been shown to be co-mitogenic for vascular smooth muscle cells (SMC) from human systemic arteries. A more modest growth-promoting effect has also been described in SMC from the bovine and porcine pulmonary circulation. Whether ET-1 has mitogenic properties in the human pulmonary circulation, and which ET receptor subtype mediates this response, is unknown. We first examined the effects of ET-1, ET-3, and the selective ETB agonist, Sarafotoxin 6c, on human pulmonary artery SMC growth. Cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(67 citation statements)
references
References 25 publications
1
66
0
Order By: Relevance
“…A major role for ET-1 in pulmonary hypertension of human newborns is also suggested by observational studies (12,13). In addition to being the most potent vasoconstrictor described to date, ET-1 has been reported to directly modulate growth in vascular smooth muscle cells (SMCs) derived from adult humans (14) and rats (15) by acting as an autocrine/paracrine mitogen. ET-1 has also been described to have anti-apoptotic effects on vascular cells derived from adult animals, including endothelial cells (16), fibroblasts (17) and systemic SMCs (18).…”
mentioning
confidence: 94%
“…A major role for ET-1 in pulmonary hypertension of human newborns is also suggested by observational studies (12,13). In addition to being the most potent vasoconstrictor described to date, ET-1 has been reported to directly modulate growth in vascular smooth muscle cells (SMCs) derived from adult humans (14) and rats (15) by acting as an autocrine/paracrine mitogen. ET-1 has also been described to have anti-apoptotic effects on vascular cells derived from adult animals, including endothelial cells (16), fibroblasts (17) and systemic SMCs (18).…”
mentioning
confidence: 94%
“…ET-1 reduces tropoelastin and LO mRNA expres- sion, and BQ 123, a specific ET A receptor antagonist, 32) can effectively prevent the effect of ET-1 on tropoelastin synthesis. ET-1 binds to ET A receptors on the cell surface, and these receptors are classical heptathelical G-protein coupled receptors that activate phospholipase C to cause hydrolysis of phosphatidyl inositol and generation of cytosolic inositol triphosphate and membrane-bound diacylglycerol, which accelerate protein kinase C (PKC) activity and intracellular Ca 2+ concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The total RNA was denatured for 1 hr at 50°C in deionized 1 M glyoxal/10 mM phosphate buffer, pH 7.0, and electrophoresed on 1% agarose gel, then was blotted to N + nylon filters (Amersham, U.K.). The membranes were hybridized for 18 hr at 42°C to 32 Plabeled probes in 50% formamide, 5 × 0.15 M sodium cloride and 0.015 M sodium citrate (SSC), 5 × Denhardt's solution, 0.1% SDS, and 250 µg/ml t-RNA. The following cDNA probes which were radioactively labeled by random priming (Amersham, U.K.) to specific activity of ϳ10 8 dpm/ µg DNA were used: chicken elastin (pTE2), 18) and β-actin (pA1).…”
Section: Metabolic Labeling and Sodium Dodecyl Sulfatepolyacrylamide mentioning
confidence: 99%
“…Intensive studies on the biochemical/physiological role of PKC over several decades have revealed that PKC activation closely linked to cell growth, cell cycle, differentiation, hormone release, reactive oxygen species (ROS) generation, and ion channels modulation (16)(17)(18)(19). Thus, PKC inhibitors are indispensable for studies on PKC-related signaling pathways.…”
Section: Biological Actions Of Pkc Inhibitors On Ion Channelsmentioning
confidence: 99%